Structural Properties of Nouns in Western Tamang - Regmi, Ambikja (Gipan, 2017)
Western Tamang (WT), a major dialect of Tamang, exhibits typologically interesting structural properties in the domain of nouns in contrast to Eastern Tamang (ET). Like in ET, the common nouns in WT are marked for gender, number, classifier and relational functions by specific markers. Unlike Himalayish languages and like ET and other Bodish languages, WT does not exhibit agreement between the subject and the verb in terms of gender and number. However, WT differs from ET, especially, in the domains of number, case markings and case syncretism.